Analgesic effect of diluted nitrous oxide in rehabilitation training of patients with burn scar contracture: Study protocol for a randomized controlled trial - Wang, Weifeng; Wang, Fei; Qiu, Xueling; Jiang, Xiaochen; Sun, Chenxi; Sun, Fan; Tang, Lu (PLOS ONE, 2025)
Background Burn patients experience severe pain when undergoing rehabilitation after skin grafting, which negatively affects their recovery. Traditional analgesic methods (such as opioids) have the risk of addictiveness and side effects. Nitrous oxide, which has rapid analgesic and sedative effects, is commonly used for conscious analgesia. The purpose of this study was to determine whether diluted nitrous oxide reduces pain compared to Placebo(oxygen) during rehabilitation after burn surgery. Method This single-center, randomized, double-blind, and controlled trial will enroll 80 patients. Patients ≥ 18 years of age who underwent rehabilitation 1 month after burn surgery with acute pain (VAS ≥ 4) were included. The main exclusion criteria included: pulmonary disease (pulmonary embolism, pneumothorax), intestinal obstruction, etc. Patients were randomly assigned in a 1: 1 ratio to intervention (A) and control (B) groups. Doctors, therapists, patients, and data collectors were unaware of the assignment outcomes. Rehabilitation will be performed by a therapist. The nurse performing the intervention handed the envelope with the patient code and the A or B assignment to the physician. Group A will receive diluted nitrous oxide inhalation plus conventional therapy (without analgesics) 30 minutes once daily for 4 weeks, and Group B will receive oxygen plus conventional therapy (without analgesics) under the same conditions. Assessments will be performed before the intervention (T0), 2 minutes (T1) and 5 minutes (T2) after the start of the intervention, and 5 minutes (T3) after the start of the intervention. The primary outcome was pain score. Secondary outcomes included vital signs, side effects, quality of life score, scar score, need for adjuvant analgesia, therapist and patient satisfaction, and willingness to receive the same gas again. Discussion If the experimental results show that diluted nitrous oxide can bring good analgesic effects without serious side effects, it can improve patients’ compliance with rehabilitation treatment and quality of life, and it is even widely implemented in hospitals and rehabilitation institutions.